Analysis of the impact of remote work on productivity and job satisfaction in multinational companies: application to Saudi Aramco (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research aims to study the impact of telework on productivity and job satisfaction in multinational companies, with a focus on Saudi Aramco. The research includes an analysis of how the remote-working model affects employee performance and job satisfaction, while exploring the factors that affect work efficiency and employee happiness. The research results showed that remote-working may improve productivity by providing a flexible work environment that helps improve time management and reduce distractions, and has contributed to increased job satisfaction due to improved work-life balance. However, some challenges were identified, such as social isolation and difficulties in collaboration, which may negatively affect the work experience. The research provides recommendations to improve the effectiveness of remote-working by enhancing digital communication tools, updating work policies, and providing continuous support and training for employees. The research indicates the need to continue studying the impact of telework and provide innovative solutions to address the challenges associated with this model.
Keywords: Telework; Productivity; Job Satisfaction; Saudi Aramco; Work-Life Balance